2016
DOI: 10.1139/cjfas-2015-0323
|View full text |Cite
|
Sign up to set email alerts
|

Energetic costs of activity in wild lake trout: a calibration study using acceleration transmitters and positional telemetry

Abstract: Acceleration telemetry transmitters offer the opportunity to estimate the cost of behaviours in free-ranging fishes, but a methodology to translate acceleration data into metabolic equivalents is still needed. This study extends previous calibration studies, explores how well tail-beat frequency transmitters fulfill their role, and presents a procedure to convert acceleration data into metabolic cost within a framework consistent with traditional fish bioenergetics models and thus facilitates comparisons of en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…First, increased reliance on Mysis and zooplankton would be less energetically efficient than foraging on larger prey fish or benthic invertebrates because predatory fish are more active when forced to feed on numerous, smaller prey (22). This increased energetic cost of feeding on small prey has been illustrated by studies that found predatory fish in lakes without pelagic prey fish had increased muscle activity and greater activity rates than those same species in lakes containing pelagic prey fish (23)(24)(25) and by studies showing that more active fish generally grow more slowly (26). Additionally, in oligotrophic lakes, the littoral zone is often more productive and smaller in volume than the pelagic zone (6,17), and therefore the probability of a lake trout's encountering prey would be higher in the littoral zone than in the pelagic zone, increasing foraging success but also reducing the time required to find prey.…”
Section: Discussionmentioning
confidence: 99%
“…First, increased reliance on Mysis and zooplankton would be less energetically efficient than foraging on larger prey fish or benthic invertebrates because predatory fish are more active when forced to feed on numerous, smaller prey (22). This increased energetic cost of feeding on small prey has been illustrated by studies that found predatory fish in lakes without pelagic prey fish had increased muscle activity and greater activity rates than those same species in lakes containing pelagic prey fish (23)(24)(25) and by studies showing that more active fish generally grow more slowly (26). Additionally, in oligotrophic lakes, the littoral zone is often more productive and smaller in volume than the pelagic zone (6,17), and therefore the probability of a lake trout's encountering prey would be higher in the littoral zone than in the pelagic zone, increasing foraging success but also reducing the time required to find prey.…”
Section: Discussionmentioning
confidence: 99%
“…This empirical work inspired some of the first theoretical studies (Kerr, ; Kerr & Martin, ) on the links between prey size, growth and life history, and lake trout has served as a model organism in several more recent theoretical treatments (Giacomini et al., ; Quince et al., ; Shuter et al., ). In addition, lake trout has also been the focus of several recent empirical tests of that theory (e.g., Pazzia et al., ; Shuter et al., ) and is particularly suited to behavioural studies using acoustic telemetry (Cruz‐Font et al., ; Guzzo et al., ; Morbey et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…The activity of 36 adult lake trout was studied using internally implanted acceleration–depth telemetry transmitters (V9AP, VEMCO, Nova Scotia, Canada; Table ). Transmitters were implanted in the posterior of the body cavity, following recommended procedures for fish (Harms, ), adapted to this type of transmitter (see Cruz‐Font et al., and Appendix S5.1 for details). Transmitter depth sensors were calibrated prior to implantation in fish.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations